Crowds in or crowds out? The effect of foreign direct investment on domestic investment in Chinese cities - Yao, Y.; Salim, Ruhul (Physica-Verlag GmbH und Co., 2018)
This study investigates the empirical relationship between foreign direct investment (FDI) and domestic investment (DI) in China using a comprehensive city-level panel over the period from 2003 to 2011. System-generalized method-of-moment estimation reveals mixed results. At the national level, FDI neither crowds in nor crowds out DI, indicating a neutral FDI–DI nexus. However, when the full sample is segmented by geographical topology, a positive and significant FDI–DI nexus can be found in eastern and, to a lesser extent, central cities. A negative, although insignificant, association is reported among western cities. Further, the empirical nexus is conditional on several local absorptive capacities including human capital, financial development, and institutional quality. These findings suggest that a region-based FDI strategy in general and local governments should strengthen their absorptive capacities to fully internalize FDI spillovers.